Pathways and modification of warm water flowing beneath Thwaites Ice Shelf, West Antarctica - Wåhlin, A. K.; Graham, A. G. C.; Hogan, K. A.; Queste, B. Y.; Boehme, L.; Larter, R. D; Pettit, E. C.; Wellner, J.; Heywood, K. J. (Science Advances, 2021)
The first oceanographic observations underneath Thwaites Ice Shelf front show previously unknown pathways for warm currents.